Rezension von: Vollmer, Franz X., Offenburg 1848/49 - Schinke, Esther (Württembergisch Franken, 2001)
Franz X. Vollmer, Offenburg 1848/49: Ereignisse und Lebensbilder aus einem Zentrum der badischen Revolution, Karlsruhe 1997. 568 S.